18F-FDG PET/CT FINDINGS IN SYNCHRONOUS DOUBLE PRIMARY LUNG ADENOCARCINOMAS: A CASE REPORT (Vietnam Journal of Community Medicine, 2026)
Synchronous double primary lung cancers are uncommon in clinical practice and are frequently misdiagnosed as pulmonary metastases. Because treatment strategies and prognosis differ significantly between these two conditions, distinguishing synchronous primary lung cancers from intrapulmonary metastatic disease is of great clinical importance. Whole-body PET/CT (Positron Emission Tomography/Computed Tomography) using the radiotracer 18F-FDG provides superior capability in assessing the metabolic characteristics of pulmonary lesions, thereby aiding in the evaluation of their malignant potential. We present a case of synchronous double primary lung cancers diagnosed based on whole-body PET/CT findings, along with a review of similar cases previously reported in the literature.
Keywords: Lung cancer; PET/CT; Multiple primary lung cancer; Synchronous MPLC; 18F-FDG; Pulmonary adenocarcinoma.